«As if they were your Vassals»: The Informal Relations of the Urban Oligarchies and the Subjugation of the Hinterland in Late Medieval Castile (SP) (Edad Media. Revista de Historia, 2017)
The subjugation of the hinterland by the city is addressed in this article from the perspective of the informal relations that were inherent to the Castilian institutional structure. Through the royal documentation, we reconstruct practices that were banned for being considered corrupt as they encouraged favors, bribes, frauds and even rioting. More particularly, we analyse some Castilian figures related to patronage, like the «criados», the «allegados» and the «acostamiento»; the extension of this model into the hinterland where the city councillors established pseudo-vassalage relations with the officers from the villages; as well as the role of gift-giving in the whole interpersonal system where custom and courtesy were inevitably confused with bribery. The paper claims that it would be misleading to conceive these behaviors as mere abuses and a perversion of politics. The patronage that benefited clients and the exchange of gifts were consubstantial to power relations in the Late Middle Ages. Therefore, the subjugation of the hinterland necessarily reproduced these same practices.
Keywords: oligarchy; city council; Castile; Late Middle Ages; hinterland; power; patronage; gift-giving